Integrated Genetic Analysis of Racial Differences of Common GBA Variants in Parkinson's Disease: A Meta-Analysis - Zhang, Yuan; Shu, Li; Sun, Qiying; Zhou, Xun; Pan, Hongxu; Guo, Jifeng; Tang, Beisha (Frontiers in Molecular Neuroscience, 2018)
Background: Numerous studies have indicated that there is a possible relationship between GBA variants and Parkinson’s disease (PD), however, most of them focused on a few variants such as L444P, N370S. We performed a comprehensive pooled analysis to clarify the relationship between variations of GBA and the risk of PD in different racial groups. Methods: Standard meta-analysis was conducted, including generating inclusion and exclusion criteria, searching literature, extracting and analyzing data. Results: 50 studies containing 20267 PD patients and 24807 controls were included. We found that variants 84insGG, IVS2+1G＞A, R120W, H255Q, E326K, T369M, N370S, D409H, L444P, R496H and RecNciI increased the risk of PD in total populations (OR: 1.78-10.49; p: <0.00001, 0.00005, 0.0008, 0.005, <0.00001, 0.004, <0.00001, 0.0003, <0.00001, <0.0001, 0.0001). In subgroup analysis by ethnicity, in AJ populations, variants 84insGG, R496H, N370S increased the risk of PD (OR: 9.26-3.51; p: <0.00001, <0.0001, <0.00001)). In total non-AJ populations, variants L444P, R120W, IVS2+1G＞A, H255Q, N370S, D409H, RecNciI, E326K, T369M increased the risk of PD (OR:8.66-1.89; p: <0.00001, 0.0008, 0.02, 0.005, <0.00001, 0.001, 0.0001, <0.00001, 0.002). Among the non-AJ populations, pooled analysis from five different groups were done separately. Variants L444P, N370S, H255Q, D409H, RecNciI, E326K increased risk of PD (OR: 6.52-1.84; p: <0.00001, <0.00001, 0.005, 0.005, 0.04, <0.00001) in European/West Asians while R120W and RecNciI in East Asians (OR: 14.93, 3.56; p: 0.001, 0.003). . L444P increased the risk of PD in Hispanics, East Asians and Mixed populations (OR: 15.44, 12.43, 7.33; p: 0.00004, <0.00001, 0.009). Lacking of enough original studies, we failed to conduct quantitative analysis in Africa. Conclusions: Obvious racial differences were found for GBA variants in PD. 84insGG and R496H exclusively increased PD risks in AJ populations, so did L444P, R120W, IVS2+1G＞A, H255Q, D409H, RecNciI, E326K, T369M in non-AJ populations. N370S increased the risk of PD in both ethnics. In non-AJ subgroup populations, N370S, H255Q, D409H, E326K exclusively increased PD risks in European/West Asians, as were R120W in East Asians. L444P increased the risk of PD in all groups in non-AJ ethnicity. These results will contribute to the future genetic screening of GBA gene in PD.